Mathematical Communication Ability by Grade VII Students Using a Themed Problem Based Learning with Scaffolding on Rectangle Materials - Saputro, Didik Adi; Masrukan, Masrukan; Agoestanto, Arief (Department of Mathematics, Universitas Negeri Semarang, 2017)
The aim of research to test students' mathematical communication used themed of PBL with scaffolding, themed of PBL and PBL achieve mastery learning;to test students' mathematical communication that used the themed of PBL with scaffolding, themed of PBL and PBL; and to test students' mathematical communication for the low, medium group, and a high-group themed of PBL with scaffolding, themed of PBL and PBL. This type of research is quantitative research. The Population is seventh grade students of SMPN 22 Semarang and the sample class VII E, F and VII VII G. Used normality test, homogenity test, equality test on average, the proportion of one-party test, one way anova test, and scheffe test. The results showed that (1) Student’s mathematical communication ability using themed of PBLwith Scaffolding strategy,themed of PBL, and PBL achieve the completeness of learning, (2) there is a difference in the classroom using the themed of PBL with scaffolding, themed of PBL, as well as PBL, (3) For the low, medium, high and there is a difference in the classroom using the themed of PBL with scaffolding, themed of PBL and PBL.